Studi Kasus Pengembangan Energi Surya Sebagai Stimulus Ekonomi Hijau 2045 - omsar rudyanto nadeak; Leonard Leonard Lisapaly; Martua Manik; Ridwan Usman (Jurnal Teknik Mesin, 2024)
To face the planetary crisis, Indonesia has prioritized sustainable development through the use of green economy practices to reduce future carbon emissions. Solar energy as one of the renewable energy sources has greater value than others, but its utilisation is still small. Consideration of this condition is discussed with the aim of evaluating the progress of the green economy; finding problems; providing solutions and suggestions for Indonesia's future development. The research method uses a systematic quantitative descriptive approach based on data collected through observations, interviews and questionnaire surveys from resource persons by providing 3 leverage factors namely; funding, regulation and institutions. The study results show that the regression coefficient of the funding factor variable (X1) is 0.365 and positive, then the funding factor variable (X1) has the largest coefficient compared to the coefficient of the regulatory factor (X2) and the institutional factor (X3), so that the funding factor is the most dominant factor in measuring the performance of solar energy success towards the implementation of the green economy. Without serious support from the government in terms of funding readiness, development goals will not be achieved, due to the large amount of funds needed to support the development of the Green Economy. However, the three variables are mutually sustainable by making policies and legal foundations to fulfil the funding needs of the green economy, regulations will be the foundation in mainstreaming the implementation and funding of green economy policies. Green economy planning, governance and supervision are supported by mature institutions and funds